ARK 1998: AWI airborne Radio-Echo Sounding data over Northeast Greenland between North GRIP and Station Nord (NOGRAM project) - Heinrich Miller; Daniel Steinhage; Veit Helm; Christoph Mayer (PANGAEA, 2025)
This dataset contains airborne radar data acquired using the AWI EMR system (Nixdorf et al., 1999) during the Arctic season of 1998. The profiles extend across the Northeast Greenland Ice Sheet between North GRIP and Station North. The data are available as netCDF files (including waveforms and metadata), KML files of the profile line locations, and quicklook images of the radargrams.